PENGARUH PERENCANAAN DESTINASI DAN PARTISIPASI MASYARAKAT TERHADAP KEBERLANJUTAN PARIWISATA DI TANJUNG KASUARI KOTA SORONG - Murni; Rasma Widya Handyni (Jurusan Akuntansi, Universitas Halu Oleo, 2026)
This study aims to analyze the influence of destination planning and community participation on tourism sustainability at Tanjung Kasuari, Sorong City. A quantitative approach using the SEM-PLS method was applied to 120 respondents selected through purposive sampling. Results indicate that: (1) destination planning has a significant positive effect on tourism sustainability (β = 0.381; T = 4.201; p = 0.000; f² = 0.158); (2) community participation has a significant positive effect on tourism sustainability (β = 0.399; T = 4.912; p = 0.000; f² = 0.173). The model explains 51.3% of tourism sustainability variance (R² = 0.513) with GoF = 0.616 (strong fit) and Q² = 0.498 (strong predictive relevance). These findings underscore the importance of synergizing comprehensive destination planning and active community participation to achieve sustainable tourism in Papua Barat Daya coastal areas.